Formulation and Evaluation of Double-layered (Matrix and Drug-in-adhesive) Transdermal Patches of Diclofenac Diethylamine: In vitro and ex vivo Permeation Studies - Sharma, Aditya; Verma, Navneet (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: The objective of this current study was to fabricate and characterize the sustained release double layered transdermal patches of Diclofenac Diethylamine using hydrophobic acrylic polymer Eudragit RL 100 and hydrophilic polymer Polyvinyl pyrrolidone K-30 in combination as first layer of matrix type patch and pressure sensitive acrylic adhesive Duro Tak 387-2510 as the second layer of drug-in-adhesive type patch to provide sustained anti-inflammatory effect. Materials and Methods: Solvent casting method was employed to prepare patch over the backing membrane. The double layered technique were attempted to create the desirable features of acrylic polymer and adhesive. The drug-polymers compatibility studies were examined by Infrared spectroscopy. A full-thickness excised abdominal rat skin sample was used to perform the permeation studies using Franz’s Diffusion Cell. Results: Drug-polymers compatibility studies revealed no evidence of interaction and the formulations showed satisfactory physicochemical-mechanical characteristics. It was found that release profiles were affected by the proportion of polymer and permeation enhancer used. The optimized formulation MF3 showed maximum in vitro and ex vivo percent cumulative drug permeated i.e. 87.28 ± 3.88% and 81.95 ± 2.64% respectively, with flux 12.96 ± 0.51 μg/cm2/h and permeability coefficient 1.09 ± 0.45 cm/h, in 24 hr. Also, the permeation studies suggested that dimethyl sulphoxide exhibit more promising results as permeation enhancer. Conclusion: It was concluded that an ideal Diclofenac Diethylamine double layered transdermal patch would serve as the best carrier to provide sustained effect with desirable permeation enhancement characteristics.
Keywords: Transdermal patches; Double layered technique; Hydrophobic acrylic polymer; Hydrophilic polymer; Permeation enhancer; Anti-inflammatory